Ideias de progresso e modernização: projetos de (re)urbanização do município de Morrinhos/GO (1950-1970) - Meira, Júlio Cesar (2017)
This thesis aims to analyze the urban restructuring projects of the municipality of Morrinhos (GO) in the second half of the twentieth century, emphasizing the administration of the Mayor Joviano Antônio Fernandes (1966-1970). Throughout the two decades, especially during the second half of the 1960s, a series of transformations took place in the city, with public power as its protagonist, intervening both from the point of view of (re) construction of urban infrastructure, in search of modern city, and the reordering of urban land occupation. These interventions had as basic ideas the search for development and modernization, from a conception of progress, as verified in the analyzes of the justifications of the draft laws of initiative of the executive sent to the City Council. The research's argument is that the (re) urbanization projects of the period surveyed were part of a discourse to retake the municipality's "vocation" for progress, which he called the period between the 1880s and 1920s when the influential political group linked to Colonel Hermenegildo Lopes de Moraes had exercised the economic and political leadership of the southern region of the state, rivaling the main oligarchies that exercised power in Goiás. In a context in which the historiography of Goias treated almost all the nineteenth century as of decadence and the Old Republic in particular as a period of delay because of the domination of the oligarchies and colonels, it is striking that local official memory has consolidated an image of progress and development for the same period, which would have been lost in the following decades and would be resumed with the urban restructuring projects in the 1960s. From the perspective of the Regime of Historicity, three in the analyzed period. A distant past from the period of the Old Republic, in which political protagonism was taken as a model of progress; A more recent past of losing the leading role to be overcome; and a gift in which the discourse of progress has chosen as the paradigm the transformation of urban structures. Because of this, the research problematizes the very notion of decadence and backwardness, as well as the representations of progress in an essentially agrarian society dominated by Colonels. The methodology includes the analysis of documentation such as decrees, ordinances and other acts of the executive power of Morrinhos, minutes of meetings of the local City Council and other devices of hegemony and use of journalistic sources. These diverse sources allowed to highlight the narratives and discourses constituting an effort to impress the progressive overcoming of the past.